Factors affecting livestock water productivity: animal scale analysis using previous cattle feeding trials in Ethiopia - Gebreselassie, S.; Peden, Donald G.; Haileslassie, Amare; Mpairwe, D.R. (Commonwealth Scientific and Industrial Research Organisation, 2009)
Availability and access to fresh water will likely constrain future food production in many countries. Thus, it is frequently suggested that the limited amount of water should be used more productively. In this study we report the results of our investigation on effects of feed, age and weight on livestock water productivity (LWP). The main objective is to identify technologies that will help enhance LWP. We combined empirical knowledge and literature values to estimate the amount of water depleted to produce beef, milk, traction power and manure. We estimated the LWP as the ratio of livestock products and services to the depleted water. In the feeding trials, various combinations of maize and oat stover, vetch, lablab and wheat bran were combined in different proportions to make 16 unique rations that were fed to the experimental animals of different age and weight groups. We observed differences of LWP across feed type, age and weight of dairy cows. The value of LWP tended to increase with increasing age and weight: the lowest LWP (0.34 US$/m3) for cows less than five years whereas the highest LWP value was 0.41 US$/m3 for those cows in the age category of 8 years and above. Similarly, there was an increase in LWP as weight of the animal increased, i.e. LWP was lowest (0.32 US$/m3) for lower weight groups (300–350 kg) and increased for larger animals. There were apparent impacts of feed composition on LWP values. For example, the highest LWP value was observed for oat, vetch and wheat bran mixes. Taking livestock services and products into account, the overall livestock water productivity ranged from 0.25 to 0.39 US$/m3 and the value obtained from a cow appeared to be higher than for an ox. In conclusion, some strategies and technological options such as improved feeds, better herd management, appropriate heard structure can be adapted to enhance LWP.